Application of the Multi-Representative Discourse Learning Model (DMR) to Numeracy Literacy Ability - Nari, Nola; Akila, Nisa (Journal Emerging Technologies in Education, 2024)
Background: The general issue in mathematics education is the suboptimal numeracy literacy skills of students, which adversely affects their learning outcomes. Improving these skills is essential for enhancing students' overall academic performance in mathematics. Purpose: This study aims to maximize students' numeracy literacy skills through the application of the Multi-Representation Discourse (DMR) learning model. The research seeks to evaluate the effectiveness of the DMR model in improving students' numeracy literacy compared to conventional teaching methods. Methods: The research methodology employs a quantitative approach using a quasi-experimental design. The instrument used in this study is a numeracy literacy skills test, with a sample consisting of two classes: an experimental group and a control group. Preliminary tests confirmed that the data met the criteria for normality and homogeneity, allowing hypothesis testing to be conducted using the t-test. Results: The research findings show that tcalculate>ttablet_{calculate} > t_{table}tcalculate?>ttable? or 3.03695 > 1.67792, leading to the rejection of H0H_0H0?. This indicates that at a 5% significance level, the numeracy literacy skills of students using the cooperative learning model type Multi-Representation Discourse (DMR) are significantly better than those of students using conventional teaching methods. Conclusion: The study concludes that the application of the DMR learning model significantly enhances students' numeracy literacy skills compared to conventional teaching methods. These results suggest that implementing the DMR model in mathematics education can lead to better learning outcomes for students.